Are the effects of hemodialysis on ocular parameters similar during and after a hemodialysis session? - Elbay,Ahmet (2017)
ABSTRACT Purpose: To evaluate the changes in several ocular parameters, including choroidal thickness, during and after hemodialysis. Methods: Twenty-seven eyes of 27 patients with chronic renal failure undergoing hemodialysis were included. The patients underwent an ophthalmic examination, including intraocular pressure, central corneal thickness, iridocorneal angle, subfoveal choroidal thickness, and blood pressure, just before a hemodialysis session, during the second hour of the session, and half an hour after the end of the session. Body weight was measured before and after the session, and ultrafiltration volume was noted after the session. Central corneal thickness, intraocular pressure, and subfoveal choroidal thickness were measured by optical coherence tomography. Results: In comparison with baseline levels, mean intraocular pressure and central corneal thickness increased significantly during the second hour of hemodialysis (p=0.001 and p=0.011, respectively) and showed no significant changes after hemodialysis (p=0.844 and p=0.246, respectively). Mean iridocorneal angle did not significantly change during the second hour of hemodialysis (p=0.101) and after hemodialysis (p=0.589). Mean subfoveal choroidal thickness was significantly lower during the second hour of hemodialysis (p<0.001) and after hemodialysis (p<0.001). Conclusions: Mean intraocular pressure and central corneal thickness increased and subfoveal choroidal thickness decreased during the second half of the hemodialysis session. During the second half of the session, intraocular pressure and central corneal thickness had a trend toward reduction, while subfoveal choroidal thickness had a relatively steady course. Because of possible fluctuations in the values, it would be reasonable to evaluate the changes not only from before to after hemodialysis but also during hemodialysis when analyzing the ocular effects of dialysis.